THE EFFECT OF ELECTRONIC SERVICE QUALITY ON MCDELIVERY MOBILE APPLICATION ON GENERATION Z CONSUMER SATISFACTION - Susilawati, Aden; Rr. Erlina (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2022)
The quality of electronic services is a matter that refers to the extent to which a company or online business has facilities related to purchasing, to the process of delivering products that are carried out effectively and efficiently. The electronic service owned by McDonald's restaurants is the McDelivery mobile application. The McDelivery mobile application is a fast food ordering application from the McDonald's company which was developed to assist marketing effectiveness and provide convenience in ordering food remotely to consumers. McDelivery mobile application on Playstore has a rating of 3+. In the review or review column in the Playstore, it shows that many of the McDelivery application downloaders gave bad reviews about this application. This shows that there is a gap between consumers and the ordering system used when the system has limitations to meet consumer needs. The purpose of this study was to determine the effect of the quality of electronic services, namely e-servqual on the McDelivery mobile application on the satisfaction of generation Z consumers. The data collection method in this study used a questionnaire distributed to all McDelivery consumers with the criteria of generation Z as many as 100 people. The results of this study support the hypothesis that e-servqual has a positive and significant effect on consumer satisfaction of Generation Z on the McDelivery mobile application. Suggestions for McDonald's to always improve the quality of electronic services (e-servqual) by improving the quality of electronic services on the dimensions of the availability system on their McDelivery mobile application